KOMUNIKASI RITUAL ZIARAH JERE PADA MASYARAKAT ADAT TERNATE MENURUT ISLAM - Harun, Rakhmat; Hanafi, Fauzan; Alhadar, Muhdi (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2024)
Abstract This article is the result of research that discusses the process of acculturation between the traditional culture of the Ternate Sultanate community and the Islamic religion. This research aims to explore the ritual communication activities of the Jere pilgrimage by the Ternate indigenous community from an Islamic perspective. This ritual is believed by the Ternate community to be in accordance with the Islamic perspective, as Islam is the majority religion and the official religion in the Sultanate of Ternate. The research approach used is descriptive-qualitative, involving the analysis of interviews with religious and traditional figures in the Sultanate of Ternate. The results of this research explain that the Jere pilgrimage is a form of ritual communication for the indigenous community of Ternate to visit the mausoleums of saints and influential figures in the spread of Islam. This research found the construction of Islamic values in the implementation of the Zere ritual and its impact on social and religious dynamics. The integration of traditional customs and Islamic teachings forms a unique pattern of ritual communication, enriching our understanding of cultural diversity and Islam in Ternate. The research provides a profound insight into the reverence of the indigenous community of Ternate towards figures and individuals regarded as saints who have made significant contributions to the spread of Islam. Furthermore, this research also found that the interaction between Islam and culture has shaped the identity of the Ternate community. This research is expected to contribute to the understanding of the social and religious context as well as cultural dynamics within the Islamic community in Ternate. Keywords: Ritual Communication, Jere Pilgrimage, Islamic Perspective